Postpractice neuromuscular performance changes in 3 × 3 professional female basketball players - Cabarkapa, D.; Cabarkapa, D. V.; Batra, A.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this investigation was to examine changes in lower body neuromuscular performance characteristics across multiple testing time points within a cohort of professional 3 × 3 female basketball players. Ten athletes volunteered to participate in this study (x¯ ± SD; age = 29.1 ± 4.3 years; height = 181.4 ± 7.0 cm; body mass = 77.4 ± 6.2 kg). Each athlete completed 3 countermovement vertical jumps while standing on a portable force plate system on 4 different occasions: before team practice, immediately postpractice, and the next morning and afternoon. Twenty-two force-time metrics were analyzed, 8 within braking and propulsive and 2 within landing phases of the jumping motion, including 4 performance metrics. Repeated measures analysis of variance was used to examine statistically significant differences (p < 0.05). The findings reveal an absence of significant changes in all force-time metrics of interest pre-post practice. However, a notable decrease in jump height (-5.8%), average and peak propulsive force (-4.3% and -4.7%), propulsive net impulse (-3.5%), average and peak propulsive power (-6.1% and -6.0%), and reactive strength index modified (-11.8%) was observed the following morning when compared with baseline measurements. The reactive strength index modified was shown to be the most sensitive metric in detecting fatigue-induced changes in athletes' performance, because it experienced the largest drop between these 2 testing time points (p = 0.011; g = 0.727). Also, the observed performance suppression disappeared by the afternoon training session because all of the aforementioned force-time metrics returned to the baseline levels, indicating that the athletes were adequately recovered to participate in team training activities.